Anorectal manometry in irritable bowel syndrome: differences between diarrhoea and constipation predominant subjects. Issue 4 (April 1990) - Prior, A; Maxton, D G; Whorwell, P J
Abstract : Anorectal manometry with balloon distension was performed on 28 patients with diarrhoea predominant irritable bowel syndrome, 27 patients with constipation predominant irritable bowel syndrome and 30 normal controls. In the diarrhoea predominant group balloon volumes required to perceive the sensations of gas, stool, urgency of defecation and discomfort were significantly lower than in controls or constipation predominant patients (p less than 0.001). Diarrhoea predominant patients also had a significantly lower rectal compliance than controls or constipation predominant patients (p less than 0.03) but showed no difference in motor activity induced by distension. When the constipation predominant patients were compared with controls the only significant difference that emerged was in the volume at which discomfort was perceived. No significant differences between constipated subjects and controls were found in the distension induced motor activity. Symptom severity and psychological parameters were also recorded and the diarrhoea predominant patients were found to be more anxious than those with constipation (p = 0.04). It proved possible (by comparison with the control group) to identify three abnormal rectal subtypes in patients with irritable bowel syndrome. These were a sensitive rectum (low sensation thresholds, normal or low rectal pressure), a stiff rectum (normal or low sensation thresholds, high pressure) and an insensitive rectum (high sensation thresholds, normal or high pressure) and their distribution varied considerably depending on bowel habit. Some form of rectal abnormality was identified in 75% of diarrhoea predominant patients compared with 30% of constipation predominant subjects (p = 0.002). A sensitive rectum was a particular feature of diarrhoea predominant patients being observed in 57% of patients compared with only 7% of the constipated group (p less than 0.001).